General Comment No. 3 on the African Charter on Human and Peoples' Rights: The Right to Life (Article 4) - Portuguese General Comment No. 3 on the African Charter on Human and Peoples' Rights: The Right to Life (Article 4) - Portuguese Adopted during the 57th Ordinary Session of the African Commission on Human and Peoples' Rights held from 4 to 18 November 2015 in Banjul, The Gambia (Pretoria University Law Press (PULP), 2016)
General Comment No. 3 on the African Charter on Human and Peoples' Rights: The Right to Life (Article 4) - Portuguese Adopted during the 57th Ordinary Session of the African Commission on Human and Peoples' Rights held from 4 to 18 November 2015 in Banjul, The Gambia 2016 ISBN: 978-1-920538-59-0 Pages: 30 Print version: Available Electronic version: Free PDF available